2003
DOI: 10.1038/sj.bjp.0705127
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of α2A‐adrenoceptor signalling by modest levels of adrenaline is facilitated by β2‐adrenoceptor‐dependent GRK3 up‐regulation

Abstract: Adrenaline (ADR) and noradrenaline (NA) can simultaneously activate inhibitory α2‐ and stimulatory β‐adrenoceptors (AR). However, ADR and NA differ significantly in that ADR is a potent β2‐AR agonist while NA is not. Only recently has the interaction resulting from the simultaneous activation of α2‐ and β2‐AR been examined at the cellular level to determine the mechanisms of α2‐AR regulation following concomitant activation of both α2‐ and β2‐ARs by chronic ADR. This study evaluates β2‐AR regulation of α2A‐AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 29 publications
3
38
1
Order By: Relevance
“…The human ␣ 2A -AR mutant (Del 293-304) that lacks the four serine residues in the third intracellular loop thought to be phosphorylated by GRKs does not acutely desensitize but does undergo down-regulation (Jewell-Motz et al, 1997). In contrast to these observations, recent studies in BE(2)-C and BN17 cells and in GRK3-and GRK2-overexpressing NG108 cells suggest that the ␣ 2A -and ␣ 2B -AR are rendered more sensitive to agonist-induced down-regulation because of a 2-to 3-fold up-regulation of GRK3 (Bawa et al, 2003;Desai et al, 2004Desai et al, , 2005. In addition, mutation of potential GRK phosphorylation sites ( 322 SSTS 325 changed to AAVA) in the third intracellular loop of opossum ␣ 2C -AR prevents receptor down-regulation after 24-h exposure to 0.3 M NE (Deupree et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The human ␣ 2A -AR mutant (Del 293-304) that lacks the four serine residues in the third intracellular loop thought to be phosphorylated by GRKs does not acutely desensitize but does undergo down-regulation (Jewell-Motz et al, 1997). In contrast to these observations, recent studies in BE(2)-C and BN17 cells and in GRK3-and GRK2-overexpressing NG108 cells suggest that the ␣ 2A -and ␣ 2B -AR are rendered more sensitive to agonist-induced down-regulation because of a 2-to 3-fold up-regulation of GRK3 (Bawa et al, 2003;Desai et al, 2004Desai et al, , 2005. In addition, mutation of potential GRK phosphorylation sites ( 322 SSTS 325 changed to AAVA) in the third intracellular loop of opossum ␣ 2C -AR prevents receptor down-regulation after 24-h exposure to 0.3 M NE (Deupree et al, 2002).…”
Section: Discussionmentioning
confidence: 88%
“…We have previously shown an increase in sensitivity of the ␣ 2A -or ␣ 2B -AR to undergo agonist-induced down-regulation after an increase in GRK levels (Bawa et al, 2003;Desai et al, 2004Desai et al, , 2005. In BN17 cells, coactivation of ␣ 2B -and ␤ 2 -AR results in a modest selective up-regulation of GRK3 and increases the sensitivity of the ␣ 2B -AR to undergo agonist-induced down-regulation (Desai et al, 2004).…”
mentioning
confidence: 93%
“…Previous results indicate that the ␣ 2 -AR may be more susceptible to the action of GRK3 than GRK2 (Diverse-Pierluissi et al, 1996;Bawa et al, 2003;Desai et al, 2004). Therefore, the sensitivity of the ␣ 2B -AR to increasing levels of GRK2 also was determined.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that GRK is not only required for ␣ 2A -and ␣ 2B -AR down-regulation, but that the sensitivity of the ␣ 2 -AR to undergo down-regulation is increased if the level of GRK is increased (Bawa et al, 2003;Desai et al, 2004). This observation is interesting for two reasons.…”
mentioning
confidence: 86%
“…The concentrations of arrestin/GRKs in cultured cells and in vivo are altered by drugs that directly or indirectly cause persistent stimulation or blockade of GPCRs [7,22,25,29,42,45,72,80,99], which implies the involvement of signaling mechanism in the regulation of the arrestin/GRK expression. The concentration GRK2, a short-lived protein, is regulated by synthesis as well as degradation, both of which are responsive to various signaling pathways (reviewed in [85,86]).…”
Section: Upregulation Of Arrestin and Grk Expression In Parkinson's Dmentioning
confidence: 99%